Association of Antenatal Depression with Clinical Subtypes of Preterm Birth - Venkatesh, Kartik K.; Ferguson, Kelly K.; Smith, Nicole A.; Cantonwine, David E.; McElrath, Thomas F. (American Journal of Perinatology, 2019)
Objective To estimate the association between antenatal depression and spontaneous preterm birth (SPTB) relative to medically indicated preterm birth (MPTB).Study Design This was a secondary analysis of a nested case–control study of preterm birth (PTB). The exposure was a clinical diagnosis of antenatal depression. The outcome was PTB at <37 weeks classified as SPTB (spontaneous labor, preterm premature rupture of membranes, placental abruption, and cervical shortening); and MPTB (preeclampsia and intrauterine growth restriction). Multinomial logistic regression models compared women without PTB versus MPTB and SPTB, adjusting for age, race, parity, tobacco use, insurance status, and prepregnancy body mass index, and history of PTB for SPTB.Results Among 443 pregnant women, 15.6% had an SPTB and 8.6% had an MPTB, and 16% were diagnosed with antenatal depression. Women with an SPTB were three times more likely to have antenatal depression compared with women without an SPTB (adjusted odds ratio [AOR]: 2.81; 95% confidence interval [CI]: 1.40–5.63). No significant association was identified between antenatal depression and MPTB (AOR: 1.77; 95% CI: 0.67–4.62). The association between antenatal depression and SPTB did not change after adjusting the aforementioned model for a history of PTB and antidepressant use.Conclusion Antenatal depression may differentially affect the risk of PTB through an increase in the odds of SPTB. These results have implications for future studies on prevention and treatment options for depression and PTB.
Keywords: pregnancy; depression; preterm birth